HIV prevalence, sociodemographic, and behavioral correlates and recruitment methods among injection drug users in St. Petersburg, Russia. - Shaboltas, Alla V; Toussova, Olga V; Hoffman, Irving F; Heimer, Robert; Verevochkin, Sergei V; Ryder, Robert W; Khoshnood, Kaveh; Perdue, Tom; Masse, Benoit R; Kozlov, Andrei P (Journal of acquired immune deficiency syndromes (1999), 2006)
In St. Petersburg, Russia, we sought to describe the characteristics of active high-risk injection drug users (IDUs) to evaluate the associations between behavioral and demographic characteristics and HIV-1 infection and to describe 3 discrete recruitment methods.
Keywords: Adult; Cohort Studies; Female; Heroin Dependence; HIV Infections; HIV Seronegativity; HIV Seroprevalence; Humans; Male; Needle Sharing; Risk Assessment; Risk-Taking; Russia; Socioeconomic Factors; Substance Abuse, Intravenous; Urban Population